Assessment of the retail outlet choice and buying behavior of fresh fruit and vegetable buyers in General Santos City - Rivera, Ray B.
Since the retail industry continues to evolve, modernize and expand, the changes in the way consumers behave are apparent. In this study, two retail outlets were considered: namely Supermarket and Wet market since these retail types are the dominant players when it comes to retailing fresh fruits and vegetables in the chosen locale of the study.The retail outlet choice and fresh fruit and vegetable (FFV) buying behavior of consumers in General Santos City were analyzed using primary data.The information was elicited through household survey. Key-informant interviews were also done to augment the analysis of the study. The results from the Bivariate Tobit Model showed that the significant factor in the shopping behavior of those buyers who procure vegetables from wet market is the price of the commodity while for those who buy their fresh fruits from supermarkets, the speed of service was identified significant among the retail outlet attributes that were considered. These factors were perceived to be the primary drivers of customers to the said retail outlets based on the econometric output. Since customers are generally sensitive to price and are time-conscious, therefore, they would opt to buy from the retail option that could best serve the value of their money and time. From the result of this study, the buying trend of FFV shoppers are constantly changing and varying depending on their preference which held more pressure on the retail outlets regarding their capacity to compete in the market.Hence, the ability of a retail outlet to formulate customer-centric schemes in order to meet the demands of the consumers could provide them with positive impacts.
Keywords: Vegetable buyers -- General Santos City(Philippines) -- Behavior; Fruits, fresh -- General Santos City(Philippines) -- Buyers -- Behavior; Vegetables -- General Santos City(Philippines) -- Stores, retail; Fruits,fresh -- General Santos City(Philippines) -- Stores, retail